Insect herbivory dampens Subarctic birch forest C sink response to warming - Silfver, Tarja; Heiskanen, Lauri; Aurela, Mika; Myller, Kristiina; Karhu, Kristiina; Meyer, Nele; Tuovinen, Juha-Pekka; Oksanen, Elina; Rousi, Matti; Mikola, Juha (Nature Communications, 2020)
Abstract Climate warming is anticipated to make high latitude ecosystems stronger C sinks through increasing plant production. This effect might, however, be dampened by insect herbivores whose damage to plants at their background, non-outbreak densities may more than double under climate warming. Here, using an open-air warming experiment among Subarctic birch forest field layer vegetation, supplemented with birch plantlets, we show that a 2.3 °C air and 1.2 °C soil temperature increase can advance the growing season by 1–4 days, enhance soil N availability, leaf chlorophyll concentrations and plant growth up to 400%, 160% and 50% respectively, and lead up to 122% greater ecosystem CO 2 uptake potential. However, comparable positive effects are also found when insect herbivory is reduced, and the effect of warming on C sink potential is intensified under reduced herbivory. Our results confirm the expected warming-induced increase in high latitude plant growth and CO 2 uptake, but also reveal that herbivorous insects may significantly dampen the strengthening of the CO 2 sink under climate warming.